PENGARUH KREDIBILITAS INFLUENCER MARKETING MELALUI MEDIA SOSIAL INSTAGRAM TERHADAP KEPUTUSAN PEMBELIAN DESSERT BOX BITTERSWEET BY NAJLA : Survey kepada followers akun Instagram Keanuagl - Ni Komang Sukma Dewi Febriyanti, (2021)
Currently, the use of influencers has become a very attractive marketing trend to support success in promotional activities through Instagram social media. Influencers who have credibility will certainly be able to influence consumer purchasing decisions for a product. Therefore, this study was conducted to examine the Effect of Influencer Marketing Credibility through Instagram Social Media on Purchase Decisions for Bittersweet By Najla dessert boxes (Survey to followers of Keanuagl's Instagram account). The theory used in this study is Source Credibility Theory, where this theory assumes that a person will be more easily persuaded when the sender of the message (the communicator) shows himself as a credible person. This study uses several research concepts including Promotion Mix, Source Credibility, Social Media, Influencer marketing and Purchase Decision. This study uses a quantitative approach with a survey method distributed to 100 respondents from followers of the Instagram @Keanuagl social media account via direct messages. The results of the study based on the Correlation Test showed that there was a low-level relationship between Influencer Marketing Credibility (X) and the Purchase Decision of Bittersweet By Najla Dessert Box (Y). Meanwhile, the results of the Coefficient of Determination Test show that the magnitude of the influence produced by Keanuagl as Influencer Marketing (X) on the Purchase Decision of the Bittersweet dessert box by Najla is 4.5%, while the other 95.5% is influenced by other factors outside of the X variable and the other variables Y which was not done in this study. Thus, the credibility of Keanuagl's influencer marketing influences the decision to purchase the Bittersweet By Najla dessert box.